Knowledge on brain death and organ donation among medical students in Belo Horizonte - Oliveira Júnior, Ronaldo Eustáquio de; Saldanha, Bruno Oliveira; Oliveira, Ana Paula Pereira de; Santos, Eduardo Antunes dos; Oliveira, Marcela Pereira; Pereira, Walter Antonio; Simão Filho, Charles (Brazilian Journal of Transplantation, 2009)
Purpose: To assess the knowledge of medical students from the 1st, 6th and 12th semesters of the course on brain death and organ dona- tion. Method: From a cross-sectional descriptive study, a questionnaire with 25 questions was applied to 248 students from 5 Medicine Schools in Minas Gerais along June 2009, to measure the knowledge of medical students on the brain death and organ donation criteria. Results: Among the respondents, 53.2% affirm they don’t remember attending a class on brain death along the course. Such percentage is only 25%, when considering only students of the last year. It was found a prevalence of only 8.9% students who affirm to have a very good knowledge on brain death and the majority (83.5%) reports to know just a little about the theme. Even among students from the 12th semester, there is ignorance on the brain death criteria, as well as the supplementary exams. In general, thirty-two per cent do not know that a supplementary examination is mandatory, and twenty percent are unaware of the need for the participation of a neurologist. Only 70.6% of all respondents know that brain death notification is required. Related to the organ donation, 98.4 per cent of all students claim to be favorable, 83.5% want to donate their organs, while 13.3% say they have never thought about the subject. However, only 61.3% have reported to their family their decision as to be or not a donor. Conclusion: The current survey demonstrates a relative ignorance of students about brain death. There is need to enhance such theme along the medical training, since those students will lead these protocols in the future. This lack of knowledge may affect the organs supply for donation, thus increasing the suffering of relatives and causing excessive expenditure for hospitals.